Identification of differentially expressed genes in omental adipose tissues of obesity and type2diabetes: A meta-analysis of microarray datasets - VETRIVEL PREETHI; MURUGESAN RAJESWARI; SENTHIL KALAISELVI; NATCHIMUTHU SANTHI (International Journal of Pharma and Bio Sciences, 2018)
The Prevalence of metabolic disorders such as obesity and diabetes has been increased throughout the world. Several studies have established the association of obesity with diabetes in terms of causative agent for insulin resistance. The role of immune system in causing adipocyte inflammation is the new area of research in identifying obesity associated insulin resistance leading to type 2 diabetes. Thus understanding the differential gene expression profile with array data in comparison of both the conditions aids in significant outcomes in clinical research. With only limited meta-analysis research performed on the estimate of obesity and type 2 diabetes, we aimed to analyze the microarray datasets of healthy obese and diabetic obese subjects to identify the differentially expressed genes and further subjected to gene ontology studies. The meta-analysis of four different microarray datasets resulted in 145 genes with differential pattern of expression. The significantly expressed genes were clustered hierarchically by comparing obese and diabetic obese individuals. The genetic ontology of the differential genes was identified in terms of functional and biological annotations showing significant mechanisms involved in inflammation. The differential genes in KEGG enriched categories of different immune response pathways were observed. In conclusion, this meta-analysis study has successfully examined the differential expression profile of microarray datasets in conditions comparing obese and diabetic obese individuals. It has shown the significance of inflammatory mediators of adipose tissue in terms of progression of insulin resistance with strong interferences linking obesity with insulin resistance. Of note, inflammation formation in adipose tissue of obese individuals with contributory roles to the etiology of diabetes has been clearly established. The contemporary data and evidence showing the incidence of type 2 diabetes in obese individuals have created hype in understanding the expression profile of both the conditions. With only limited meta-analysis research performed on the estimate of obesity and type 2 diabetes, we aimed to analyze the microarray datasets of healthy obese and diabetic obese subjects to identify the differentially expressed genes and further subjected to gene ontology studies. The results have given strong inferences showing strong associations linking obesity with insulin-resistant diabetes mediated by inflammatory responses. Of note, inflammation formation in adipose tissue of obese individuals with its contributory roles to the etiology of diabetes has been clearly established.